Difficulties of Non-English Study Program Students in Carrying Out the Institutional TOEFL Test - Gunantar, Devy Angga Angga; Rosaria, Stefani Dewi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to provide an analysis of TOEFL results and examine the challenges faced by non-English study program students when tackling TOEFL exam questions. The study adopts a descriptive qualitative approach, with a sample size of 30 students selected through purposive sampling from a larger population of 100 students. Data collection involved the administration of TOEFL tests and conducting interviews. The findings indicate that among the different sections of the TOEFL, Listening Comprehension posed the greatest difficulty for the participants, followed by Reading Comprehension and Structure and Written Expression. Based on the conclusions drawn from the data and explanations, it can be inferred that participants encountered the most challenges in the Listening Comprehension section of the TOEFL exam. Specifically, they struggled with long conversations, spoken passages, and short conversations in sequential order. The second most challenging section for students was Structure and Written Expression. Furthermore, the analysis reveals that within the three TOEFL sections, Structure was perceived as more difficult than Written Expression. In contrast, Reading Comprehension appeared to be the easiest section. The findings suggest that identifying difficult words presented the most significant challenge in Reading Comprehension, while identifying topics, explanatory sentences, and references were considered relatively easier. Overall, this study provides valuable insights into the specific difficulties faced by non-English study program students when attempting TOEFL exam questions, highlighting the areas that require further attention and support in their language learning journey